Might Corporate Social Responsibility Hollow Out Support for Public Assistance in Europe?. (3rd March 2017) - Burgoon, Brian; Fransen, Luc
Abstract: This article explores whether private regulatory activity to promote labour and social standards might hollow out traditional public regulations to provide welfare and labour protection at home and abroad. Such exploration has hitherto been frustrated by empirical limitations of measures of private regulatory activity and its implications for public regulation. The present article extends those limits by focusing on how new measures of labour‐related private regulation affect attitudes in 27 European polities towards welfare redistribution and for foreign assistance. Our analysis suggests that private‐regulatory CSR promoting labour and social standards may directly and indirectly diminish public support for domestic welfare redistribution, but appears to have little effect on support for foreign aid. We see, hence, possible crowding‐out only with respect to domestic, not international, assistance.